Accounting - to trial balance - Pascoe, Ian.; Carr, Peter (Peter W.) (South Melbourne : Nelson, 1994)
Accounting concepts and terms. Source documents and journals. Posting to the general ledger. Posting to subsidiary ledgers. Bank reconciliation. Petty cash. Payroll accounting.
Keywords: Accounting; Bookkeeping; Accounting; Accounting -- Problems, exercises, etc; Bookkeeping